Uso de la metodología de dinámica de sistemas para la mejora de la planificación de la producción de Ganado porcino en el fundo Las Malvinas. - Pineda Reátegui, José Luis (2013)
The following research "Dynamic System Methodology Usage to improve pig planning and production in Las Malvinas Farm.", aims to develop an improved System of Planning and Production of a company cattel sector specifically in the Las Malvinas farm for this purpose the analysis of business units and processes were performed to build the model and then simulated production systems. The results of the research shows that the Dynamic System Methodology usage contribute improve planning and production in the farm.